A Method for the Direct Absolute Measurement of J/ψ Decay with ψ(3686) Data Set - Fang Yan; Bo Zheng (Advances in High Energy Physics)
To take the full advantage of the ψ(3686) data set collected at e+e- collider at τ-charm energy region, a tag method is developed to directly measure the J/ψ meson decay branching fractions absolutely. The J/ψ meson decay can be measured with the J/ψ sample tagged by the two soft charged pions from the decay ψ(3686)→J/ψπ+π-. This method is illustrated by comparing the input and output branching fractions of J/ψ→γη with 106 million inclusive ψ(3686) Monte Carlo samples. The consistent result confirms the validity of the tag method.